A national cross-sectional study on effects of fluoride-safe water supply on the prevalence of fluorosis in China. Issue 5 (25th September 2012) - Wang, Cheng; Gao, Yanhui; Wang, Wei; Zhao, Lijun; Zhang, Wei; Han, Hepeng; Shi, Yuxia; Yu, Guangqian; Sun, Dianjun
Abstract : Objective: To assess the effects of provided fluoride-safe drinking-water for the prevention and control of endemic fluorosis in China. Design: A national cross-sectional study in China. Setting: In 1985, randomly selected villages in 27 provinces (or cities and municipalities) in 5 geographic areas all over China. Participants: Involved 81 786 children aged from 8 to 12 and 594 698 adults aged over 16. Main outcome measure: The prevalence of dental fluorosis and clinical skeletal fluorosis, the fluoride concentrations in the drinking-water in study villages and in the urine of subjects. Results: The study showed that in the villages where the drinking-water fluoride concentrations were higher than the government standard of 1.2 mg/l, but no fluoride-safe drinking-water supply scheme was provided (FNB areas), the prevalence rate and index of dental fluorosis in children, and prevalence rate of clinical skeletal fluorosis in adults were all significantly higher than those in the historical endemic fluorosis villages after the fluoride-safe drinking-water were provided (FSB areas). Additionally, the prevalence rate of dental fluorosis as well as clinical skeletal fluorosis, and the concentration of fluoride in urine were found increased with the increase of fluoride concentration in drinking-water, with significant positive correlations in the FNB areas. While, the prevalence rate of dental fluorosis and clinical skeletal fluorosis in different age groups and their degrees of prevalence were significantly lower in the FSB areas than those in the FNB areas. Conclusions: The provision of fluoride-safe drinking-water supply schemes had significant effects on the prevention and control of dental fluorosis and skeletal fluorosis. The study also indicated that the dental and skeletal fluorosis is still prevailing in the high-fluoride drinking-water areas in China.